Peran Dinamika Technology AI & Praktik Akuntansi Berkelanjutan Dalam Organisasi Universitas - Emi Vita Liani; Umi Soleha; Windy Nurrahmadani; Zul Azmi (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to find out the extent of identifying an organization’s ability to implement sustainable accounting, not only that, this research is also about technology and the benefits and impacts included, as well as the implications when accounting is in the context of multinational companies in Indonesia. This research process uses a qualitative method Literature review and document analysis methods. This research also explores the extent of technology adoption, the benefits and challenges involved as well as the implication of sustainable accounting processes in the context of university organizations. Therefore, this study suggests future research to review changes, as well as skill development. Apart from that, this research also contributes to the developing discourse on accounting technology-based transformation and provides insight that can be followed up for a company, for example at a university.